Bioecology of Orthogalumna Terebrants Wallwork on Waterhyacinth - Babykala P (Department of Agricultural Entomology, College of Horticulture, 1994)
The mite biology, morphology, nature of extent of damage and interaction with N. eichhorniae were studied. The might laid solitary eggs sideways to the oviposition holes, deeply embedded in the aerenchyma cells. The incubation period was 5.8 days. The larvae and nymphs fed by making galleries. The larvae, proto and deuto nymphal stages were completed in 3 days each, while that of tritonymph took 4 days. The duration of inactive stages from larva to proto, proto to deuto and deuto to tritonymphal stage were 1.6 days each, whereas from tritonymph to adult, it was 3 days. Adult longevity was 57.3 days. pre-ovipositional period was 4 days and the total number of eggs produced during the whole life period was 41.5 eggs. The larvae have three pairs of legs but no genital opening. The nymphal stages have four pairs of legs, ending in single claws. The proto, deuto and tritonymphal stages, have one, two and three pairs of genital papillae respectively. This character helps in identification of larval and nymphal stages. The adults are pteromorphs and sexual dimorphism is absent. Sensillus is relatively short with curved stem and globular roughened head. Terminally the tarsus of the leg has three claws on a short peduncle the lateral claws more slender than the median and sharply angled. The larval and nymphal feeding produces galleries on leaves of waterrhyacinth resulting in brown streaks on the leaf lamina. Such brown streaks later coalesce to form large brown areas, leading to drying up of the entire leaf. As the mite load increased from ten to eighty the number of plants and number of leaves showed significant reduction 90 days after release. The extent of damage caused by O. terebrantis with or without weevil under open and partially shaded conditions of waterhyacinth plants was experimented upon, and it showed that, the root length, petiole length ( in open condition), laminar width and length, number of leaves and number of plants under both light intensities (partially shaded and open condition), in general showed a decreasing trend. The plants in tanks having ten weevils alone per tank and 10 weevils plus 100 mites per tank under partially shaded conditions collapsed within 60 days, whereas in open condition of that having 10 weevils plus 100 mites per tank, all the plants collapsed by the 75th day. In the treatment with ten weevils alone per tank in open condition the collapse occurred only at 105 days. In the treatment with 100 mites alone per tank, there was no collapse of plants upto 105 days (in both conditions). The number of mite galleries and mite population per leaf with Neochetina feeding marks was comparatively more in the presence of weevils than in their absence. Fungi like Fusarium, Aspergillus and Rhizopus were isolated and also the spider mite and insects like aphids and grasshoppers were noticed.